Analysis of metabolic flux in felid spermatozoa using metabolomics and 13C-based fluxomics†. Issue 5 (30th January 2019) - Weiner, Halli S; Crosier, Adrienne E; Keefer, Carol L
Abstract: Spermatozoa from three feline species—the domestic cat ( Felis catus ), the cheetah ( Acinonyx jubatus ), and the clouded leopard ( Neofelis nebulosa )—were analyzed using metabolomic profiling and 13 C-based fluxomics to address questions raised regarding their energy metabolism. Metabolic profiles and utilization of 13 C-labeled energy substrates were detected and quantified using gas chromatography–mass spectrometry (GC-MS). Spermatozoa were collected by electroejaculation and incubated in media supplemented with 1.0 mM [U 13 C]-glucose, [U 13 C]-fructose, or [U 13 C]-pyruvate. Evaluation of intracellular metabolites following GC-MS analysis revealed the uptake and utilization of labeled glucose and fructose in sperm, as indicated by the presence of heavy ions in glycolytic products lactate and pyruvate. Despite evidence of substrate utilization, neither glucose nor fructose had an effect on the sperm motility index of ejaculated spermatozoa from any of the three felid species, and limited entry of pyruvate derived from these hexose substrates into mitochondria and the tricarboxylic acid cycle was detected. However, pathway utilization was species-specific for the limited number of individuals (four to seven males per species) assessed in these studies. An inhibitor of fatty acid beta-oxidation (FAO), etomoxir, altered metabolic profiles of all three felid species but decreased motility only in the cheetah. While fluxomic analysis provided direct evidence that glucose and fructose undergo catabolic metabolism, other endogenous substrates such as endogenous lipids may provide energy to fuel motility. Abstract : Fluxomic analysis demonstrated that glucose, fructose, and pyruvate are metabolized by ejaculated spermatozoa of domestic cats ( Felis catus ), cheetahs ( Acinonyx jubatus ), and clouded leopards ( Neofelis nebulosa ), but pathway utilization is species-specific.